The Effect of Temperature and Roasting Time on The Physical Properties of Arabica and Robusta Gayo Coffee Bean - Elin Yusibani; Ikramullah ikramullah; Evi Yufita; Zulkarnain Jalil; Endi Suhendi (Green Engineering Society, 2023)
The effect of variations in temperature and roasting time on the physical properties of coffee beans originating from the Gayo highlands with Arabica and Robusta types have been studied in this paper. Physical properties measured include weight loss, true density, porosity, and water content. The measurement procedure follows Standard Nasional Indonesia (SNI) 01-2907-2008. Three roasting levels were used in this study, i.e., Light Roast (159 -164 °C), Medium Roast (211 - 215 °C), and Dark Roast (above 232 °C) by an oven. The result showed that the weight loss for Arabica and Robusta coffee beans is from 11 - 19% and 14 - 29%, respectively. The true density for Arabica and Robusta coffee beans ranged from 0.905 - 1.085 g/cm3 and 0.950 - 1.156 g/cm3, respectively. The difference in porosity changes before and after roasting was 23 - 73% for Arabica and 33 - 68% for Robusta coffee beans. Meanwhile, the water content of Arabica and Robusta coffee beans after roasting is 0.7 - 5% and 0.6 - 6%, respectively. The value of the weight loss, true density, and water content of Arabica is lower than that of the Robusta coffee bean, while the porosity value of Arabica is higher than that of the Robusta coffee bean.